Luminescent Polynuclear Zn- and Cd-Ln Square-Like Nanoclusters With a Flexible Long-Chain Schiff Base Ligand - Zhu, Ting; Yang, Xiaoping; Zheng, Xiaohui; Wang, Shiqing; Bo, Le; Wang, Chengri; Chen, Hongfen; Jiang, Dongmei; Schipper, Desmond (Frontiers in Chemistry, 2018)
Two series of Zn-Ln and Cd-Ln nanoclusters [Ln4Zn8L2(OAc)20(OH)4] [Ln = Nd (1), Yb (2), and Sm (3)] and [Ln2Cd2L2(OAc)2(OH)2(OCH3)2] [Ln = Nd (4), Yb (5), and Sm (6)] were prepared using a long-chain Schiff base ligand with a flexible (CH2)2O(CH2)2O(CH2)2 chain. All these clusters show square-like structures. The Schiff base ligands show “linear” configurations in the structures of 1-6, and the metric dimensions of Zn-Ln and Cd-Ln clusters measure ~8 × 14 × 21 and 8 × 12 × 12 Å, respectively. The study of luminescence properties shows that the Zn/L and Cd/L chromophores can effectively transfer energy to the lanthanide ions, and 1-6 show visible and NIR emissions.